Inventory of the Cerambycidae species (Coleoptera) from Vila Dois Rios (Ilha Grande, Angra dos Reis, Rio de Janeiro, Brazil) - Rodrigues, Juliana Mourão dos Santos; Monné, Miguel Angel; Mermudes, José Ricardo Miras (Biota Neotropica, 2010)
A survey of the Cerambycidae species recorded in Vila Dois Rios (Ilha Grande, Angra dos Reis, Rio de Janeiro, Brazil) is presented. The work was based on seven collects from January to December 2008, literature data and material housed in the Museu Nacional, Universidade Federal do Rio de Janeiro. Three subfamilies are recognized and all the 50 species are new records for Ilha Grande. Catalographic information, distribution, illustration and examined material are given. Prioninae with three species and three genera in two tribes, Mallaspini (Pyrodes) and Macrotomini (Mallodon, Mercosarthron), it represents 6% of all species. Cerambycinae with seven species and seven genera in five tribes - Callichromatini (Callichroma), Cerambycini (Poeciloxestia, Sphallotrichus), Elaphidiini (Ambonus, Eurysthea), Heteropsini (Mallosoma), Hexoplonini (Gnomidolon)- it represents 14%. Lamiinae, with 40 species in 29 genera and ten tribes - Acanthocinini (Alcidion, Lophopoeum, Nealcidion, Nyssodrysina, Nyssodrysilla, Nyssodrysternum, Pentheochaetes, Trichillurges, Tropidozineus, Urgleptes), Acanthoderini (Macronemus, Oreodera, Psapharochrus) Agapanthiini (Hippopsis, Pachypeza), Anisocerini (Onychocerus), Apomecynini (Adetus, Amphicnaeia, Falsischnolea, Rosalba), Colobotheini (Colobothea), Desmiphorini (Estola, Estolomimus), Hemilophini (Malacoscylus), Onciderini (Hesycha, Hypsioma, Ischiocentra, Peritrox) and Pteropliini (Esthlogena) - it represents about 80% of the total species.